STUDI TUTUPAN KARANG DI PULAU JANGGI KECAMATAN TAPIAN NAULI KABUPATEN TAPANULI TENGAH PROVINSI SUMATERA UTARA Study of Lifeform Coral in Janggi Island Tapian Nauli Subdistict District of Tapanuli Tengah, North Sumatera Province - Nanda Rizki; Hasan Sitorus; Zulham Apandy (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2016)
NANDA RIZKI. Study of Lifeform Coral in Janggi Island Tapian Nauli Subsistrict, District of Tapanuli Tengah, Sumaterea Utara. Under Academic Supervision by HASAN SITORUS and ZULHAM APANDY HARAHAP.Janggi Island at Tapian Nauli subdistrict, District of Tapanuli Tengah is one small island and a part of Mursala Island as the main island. The aims of the study are to analize the percentage of coral covered area and the condition of coral reefs ecosystem in the Janggi Island. The research used survey method by using line intercept transect (LIT) in two research stations with line transect 70 meters and three replications in each transect. Guidelines for measuring the condition of coral refers to Keputusan Badan Pengendalian Dampak Lingkungan Hidup No. 47 of 2001. The results showed the condition of coral reefs in the Janggi island was good health category with coral covered area of 56,93%. The result increased if it compared to monitoring that conducted by Marine and Fisheries Department of North Sumatera in 2012 (46,83%). The lifeform coral percentages were included into the category Hardcoral Non-acropora to cover a percentage of 39,73% at the first station and 46,20% in the second station, which was dominated by coral massive (CM).Keywords: coral covered area, Janggi Island, Tapanuli Tengah